Mock Page: Standardized Patient Case - Merry Markham; Erik Black; Julia Close; Lou Ann Cooper; Gwen Lombard; Lynne Meyer; Casey White; Carolyn Stalvey (Association of American Medical Colleges, 2015)
Abstract This single-station, standardized case assesses the medical knowledge and communication skills of an intern and/or fourth-year medical student in answering a mock page. The authors developed this case as an objective method to assess professionalism and communication skills through the use of a common clinical scenario in the health care system: a page from a nurse about patient care (an infected central venous catheter). This case can be administered as a stand-alone assessment or included as a station in an OSCE. The mock page scenario was created to mimic a naturally occurring communication episode between the learner and a nurse. In this scenario, a standardized nurse was used in the interaction. The authors created a checklist to emphasize items that demonstrate professionalism and communication skills. Medical knowledge checklist items were developed to assess the learner's ability to correctly identify and manage the clinical scenario of an infected indwelling venous catheter. This station was part of a six-station OSCE performed during the fourth-year medical school sub-internship rotation. This case has also been used during OSCEs administered to residents at the beginning and end of the intern year. Each examinee was provided with written instructions on the door of the station room. Using the checklist, in which items were equally weighted, the nurse assessed each learner during a 3-minute break between interactions. Scores were reported as percent correct on the 12-item checklist. Formative educational feedback on students' performance was provided to the learner, the sub-internship directors, and the director of the fourth year. Feedback on the interns' performance was provided to the interns and to their program directors. This feedback allowed medical students to identify areas for self-improvement as they progressed to the intern year, and it allowed individual program directors to reflect on and potentially modify their educational curricula.